Mapping the Research Landscape: A Bibliometric Analysis of Islam's Role in Sustainable Development - Saky, Sheikh Abu Toha Md; Azani, Mohammad Zakki; Shohib, Muhammad Wildan; Islam, Md Nurul (Prisma Sains : Jurnal Pengkajian Ilmu dan Pembelajaran Matematika dan IPA IKIP Mataram, 2024)
This bibliometric analysis delves into the expansive landscape of research where Islam intersects with sustainable development, covering the period from 1991 to 2023. The dataset, comprising 586 documents from 354 sources, signifies a dynamic and rapidly growing field, with an impressive annual growth rate of 11.44%. The relatively low average document age of 5.08 years highlights the contemporary nature of the research, while the high average citations per document (5.795) and substantial reference count (25,019) underscore the field's influence and interconnected character. Key contributors include Malaysia, with 369 articles, and Indonesia with 269 articles, emphasizing their leadership roles. The USA emerges as the most cited country, with 284 total citations, reflecting its significant impact. The global collaboration map highlights Malaysia as a central hub, collaborating notably with Indonesia, Bangladesh, and the USA, illustrating the collaborative nature of research in this area. Trending topics reveal a shift towards holistic themes like environmental protection, ethics, and public health. The enduring presence of keywords such as "sustainable development" and "Islam" underscores central themes, providing valuable insights into the evolving discourse. These discoveries have important ramifications for scientific education, strengthening tactics and curriculum via a deeper comprehension of sustainable development in Islamic contexts. This research fosters a more comprehensive approach to sustainability education by addressing global concerns with cultural and religious components and bridging multidisciplinary barriers by clearly highlighting these links. This increases the study's applicability to a wide variety of multidisciplinary audiences, such as academics, educators, and decision-makers who want to improve scientific education within Islamic contexts.